Penerapan Inovasi Layanan Si Anti Ribet di Kantor Kejaksaan Negeri Kota Surabaya - Meita Dian Parmidi; Nihayatus Sholichah; Ika Devy Pramudiana (Universitas Dr. Soetomo Surabaya, 2022)
Si Anti Ribet Innovation (Ready to Deliver Tickets to Home Quickly) is a staffing innovation based on website technology on mobile phones that is useful for verifying data regarding ticket cases to make it easier for people to deal with ticket problems. The Si Anti-Ribet program aimed at people who are ticketed, so they don't need to go to the Surabaya District Attorney's Office to collect a ticket document in the form of a vehicle registration certificate (STNK), but simply by accessing the provided link. The purpose of this study was to find out the application of service innovation as well as the inhibiting and supporting factors in the implementation of Si Anti-Ribet service innovation at the Surabaya District Attorney's Office. The type of research used is descriptive research with a qualitative approach. Data collection techniques consist of observation, interviews, documentation. Data analysis techniques were carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the study show that the Anti-Ribet innovation service at the Surabaya City Public Prosecutor's Office has been going well. and helped the community a lot in solving ticket problems. the community can facilitate access to the latest information, accelerate the flow of information and greatly facilitate communication between individuals, both far and near.